Digital Forensics: Focusing on Image Forensics - Khalaf, Rayan Sulaiman; Varol, Asaf (Ieee, 2019)
The world is continuously developing, and people's needs are increasing as well; so too are the number of thieves increasing, especially electronic thieves. For that reason, companies and individuals are always searching for experts who will protect them from thieves, and these experts are called digital investigators. Digital forensics has a number of branches and different parts, and image forensics is one of them. The budget for the images branch goes up every day in response to the need. In this paper we offer some information about images and image forensics, image components and how they are stored in digital devices and how they can be deleted and recovered. We offer general information about digital forensics, focusing on image forensics.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: image; forensics; investigations; processing; digital; cyber